MISKONSEPSI DAN SIKAP SISWA PADA PEMBELAJARAN LEMAK MELALUI PRAKTIKUM PEMBUATAN SABUN TRANSPARAN - Kadarohman, Asep; Nahadi, Nahadi; M., Mira Ratna Asri (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
The students’ misconceptions and attitudes in teaching learning fat through transparent soap-making lab has been investigated. The study was conducted on 36 science students on the 3th grade at one of the state senior high school in Bandung. The research used descriptive method, with diagnostic tests, questionnaires attitude scale